Lactate dehydrogenase (LDH) isozymes of human atherosclerotic plaques. - Gown, A. M. (1982)
We have been searching for additional markers to explore differences between the smooth muscle cells of human atherosclerotic fibrous plaques and their putative cells of origin in an aortic media and intima. Lactate dehydrogenase (LDH) isozyme analysis was performed on samples of human fibrous plaques selected by gross and microscopic criteria, and significant shifts in M4/M2H2 LDH isozyme ratios were found, relative to the underlying media and adjacent intima specimens. These changes are in the same direction seen in neoplastic tissues in vitro and in vivo and are probably not secondary to positional factors, inflammatory changes, or degenerative changes. The significance of these findings in relation to the monoclonal hypothesis of atherosclerosis is discussed.